Ambulance Calls for Substance-Related Issues Before and After COVID-19. (2nd November 2021) - Weiner, Scott G.; Cash, Rebecca E.; Hendricks, Michelle; El Ibrahimi, Sanae; Baker, Olesya; Seethala, Raghu R.; Peters, Gregory; Goldberg, Scott A.
Abstract: Background : The United States is currently facing 2 epidemics: sustained morbidity and mortality from substance use and the more recent COVID-19 pandemic. We tested the hypothesis that the pandemic has disproportionately affected individuals with substance use disorder by evaluating average daily 9-1-1 ambulance calls for substance use-related issues compared with all other calls. Methods : This was a retrospective cross-sectional analysis of 9-1-1 ambulance calls before and after the start of COVID-19 in Massachusetts. We used consecutive samples of 9-1-1 ambulance calls, categorized into those which were substance-related or not. An interrupted time series analysis was performed to determine if there were changes in numbers of daily calls before a statewide declaration of emergency for COVID-19 (February 15–March 9, 2020), from the emergency declaration until a stay-at-home advisory (March 10–March 22, 2020) and following the stay-at-home advisory (March 23–May 15, 2020). Results : Compared with prior to the statewide emergency, the post-statewide emergency average of daily ambulance calls decreased from 2, 453.2 to 1, 969.6, a 19.7% decrease. Similarly, calls for substance-related reasons decreased by 16.4% compared with prior to the statewide emergency. However, despite an initial decrease in calls, after the stay-at-home advisory calls for substance use began increasing by 0.7 (95% confidence interval (CI) 0.4–1.1) calls/day, while calls for other reasons did not significantly change (+1.2 (95% CI −0.8 to 3.1) calls/day). Refusal of transport for substance-related calls increased from 5.0% before the statewide emergency to 7.5% after the declaration ( p < 0.001). Conclusions : After an initial decline in substance-related ambulance calls following a statewide declaration of emergency, calls for substance use increased to pre-COVID-19 levels, while those for other reasons remained at a lower rate. The results suggest that COVID-19 is disproportionately affecting individuals with substance use disorder.